The Effectiveness of Da'wah Approach Through Multimedia Among College Students Alumni of Ibrahimy University, Indonesia - Rahmat Saputra (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
Today we have been living with multimedia, something that we can not ignore. Even, most of us can not live without it. Multimedia have changed many things in our lives. We can listen to the music, view pictures, and watch videos from various platforms. Despite offering so many facilities, multimedia can be very dangerous for college students in the booming of social media and social chat. College students alumni in East Java prefer to enjoy multimedia through Facebook platform rather than another conventional platform. Therefore, da'wah in the present of time has a very big challenge among college students. Without the right approach, da’wah by utilizing multimedia has no significant impact. This research is a quantitative research that tests the effectiveness of da'wah approach through text, image, and video and through facebook platform as a mediator among college students alumni. The purpose of this research is to know the effectiveness of da'wah approach that college students alumni are interested in. The population of this research is college students alumni who use facebook located in the province of East Java, Indonesia. Respondents of this research amounted to 100 people as samples taken from alumnus of Ibrahimy University. Questionnaires are used as data collection methods. Data analysis method used is Structural Equation Modeling (SEM) using IBM SPSS Amos software. The result of this research show that facebook platform has a significant impact on college students alumni interest in da'wah approach through multimedia. It’s mean video, picture, and text had a significant effect on Facebook platform. The results of this research can be used as a reference by the Islamic practitioners both individual and institutional who want to make da’wah through multimedia have positive impact.